2020
DOI: 10.1186/s12905-020-01096-1
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and factors associated with early discontinuation rate of Implanon utilization among women who ever used Implanon in Kucha District Gamo Gofa Zone, Southern Ethiopia

Abstract: Background The promotion of contraception in countries with high birth rates has the potential to reduce poverty, hunger, maternal, and childhood deaths. Every year in sub-Saharan Africa approximately 14 million unintended pregnancies occurred and a sizeable proportion was due to poor use of short-term hormonal methods. Contraceptive hormonal implants are highly effective and suitable for almost all women at any stage of their reproductive lives. On the other hand, early discontinuation of the Implanon contrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 12 publications
(17 reference statements)
4
12
0
Order By: Relevance
“…46 This high rate of discontinuation might be due to inadequate pre-insertion counseling and post-insertion follow-up, as well as minimal male partner involvement before insertion, as seen in the majority of the included studies in this systematic review and meta-analysis. 31,35,37 Also, this could be due to a decreased need for contraception, dissatisfaction with the current methods, or poor management of side effects. 42 This high rate of discontinuance could also be due to the good/cheap access to implant removal services in Ethiopia, as compared to other countries where women may not have this option.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…46 This high rate of discontinuation might be due to inadequate pre-insertion counseling and post-insertion follow-up, as well as minimal male partner involvement before insertion, as seen in the majority of the included studies in this systematic review and meta-analysis. 31,35,37 Also, this could be due to a decreased need for contraception, dissatisfaction with the current methods, or poor management of side effects. 42 This high rate of discontinuance could also be due to the good/cheap access to implant removal services in Ethiopia, as compared to other countries where women may not have this option.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 11 cross-sectional studies were included in this systematic review and meta-analysis. [28][29][30][31][32][33][34][35][36][37][38] A total of 4320 Implanon users were considered in the meta-analysis. In all of the studies, data were collected by a face-to-face interview using a pre-tested, interviewer-administered questionnaire.…”
Section: Characteristics Of Identified Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…17 From 13 articles included in this systematic review and meta-analysis, only four regions of Ethiopia were identified. Of the total studies included, four were conducted in Amhara; 16,[18][19][20] four in South Nations Nationalities and Peoples of Ethiopia national (SNNPR), 17,[21][22][23] three studies in Oromia [24][25][26] and two in Tigray. 27,28 Six studies were conducted in urban areas and the rest seven were conducted in rural areas.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…To date, the prevalence of implant discontinuation rate in Ethiopia ranges from 16% to 66%. [16][17][18][19][20][21][22][23][24][25][26][27][28] However, those studies offered district-level information and there is no updated national representative evidence regarding the overall discontinuation rate about all types of implant contraceptives. So it is practical to work on synthesizing the evidence.…”
Section: Introductionmentioning
confidence: 99%